2021
DOI: 10.1002/zaac.202000453
|View full text |Cite
|
Sign up to set email alerts
|

Applications of metal‐organic frameworks and zeolites to virus detection and control: biosensors, barriers, and biocomposites

Abstract: Viruses affect humanity causing deaths and economic problems all over the world. Metal‐organic frameworks (MOFs) and zeolites are nanoporous compounds that can be tailor‐synthetized to specific applications to detect and control virus infections. Three main applications are found for these materials towards viruses: biosensors, barriers and biocomposites. Biosensors based on MOFs and zeolites possess a high selectivity in fluorescence assays to detect virus genetic material. Barriers based on modified zeolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Although the fabric modified with zeolite A did not show antiviral effects, in the case of fabric modified with Cu 2+ , it was capable to inactivate the Ck/Yamaguchi/7/04 H5N1 virus in a short incubation time, and also in the case when the virus was recovered immediately from the textile. In a similar way, Aguilar Palma et al [ 22 ] reported the use of zeolite A for modification of a textile consisting of 100% cotton in this case, the Na+ ion was also replaced by Cu 2+ . The zeolite incorporated into the textile lasted for one dozen washings.…”
Section: Introductionmentioning
confidence: 88%
“…Although the fabric modified with zeolite A did not show antiviral effects, in the case of fabric modified with Cu 2+ , it was capable to inactivate the Ck/Yamaguchi/7/04 H5N1 virus in a short incubation time, and also in the case when the virus was recovered immediately from the textile. In a similar way, Aguilar Palma et al [ 22 ] reported the use of zeolite A for modification of a textile consisting of 100% cotton in this case, the Na+ ion was also replaced by Cu 2+ . The zeolite incorporated into the textile lasted for one dozen washings.…”
Section: Introductionmentioning
confidence: 88%
“…In a recent review by Aguilar-Palma, Roy, and other researchers, it was mentioned that zeolites and MOFs may be applied to textiles and plastics to avoid virus spread in water and air. 107 These composites contain heavy metals, and/or metals that can act as biocide antiviral agents such as silver(I), copper(II), and zinc(II) are of interest in such macroscopic physical barriers.…”
Section: Isolationmentioning
confidence: 99%
“…Indeed, without access to host cells, the virus dies and cannot replicate, whereas bacteria do not express this need. This general approach of virus isolation has been the subject of some interest recently, 107 and can be accomplished in a variety of manners. Indeed, the virus can be adsorbed at the MOF surface or within the pores, mineralized under a coating of MOF crystals, or barred access by a physical barrier.…”
Section: Isolationmentioning
confidence: 99%
“…In a stability study by Velásquez-Hernández and coworkers, the immersion of ZIP-8 MOFs in PBS (10 mM) led to a break of the coordination bond, destroying the MOF structure [ 96 ]. In some MOF types, the presence of a specific functional group (aromatic rings, charged moiety, hydrogen-containing group) on their large surface may promote aspecific binding with any interfering substance through π–π stacking, hydrogen binding, or ionic interaction [ 97 ]. As MOF materials are mainly insulators or semiconductors, their low conductivity becomes the primary constraint that needs to be addressed before employing them in an electrochemical detection platform.…”
Section: Comparison Of Nanocarriers and Their Challengesmentioning
confidence: 99%